23 Longitudinal but not circumferential strain is associated with healthy ageing: a strain-encoded cardiac magnetic resonance imaging study at 3.0TESLA. (26th April 2015) - Mangion, Kenneth; Clerfond, Guillaume; Carrick, David; McClure, John; Rauhalammi, Samuli M; Corcoran, David; McComb, Christie; Radjenovic, Aleksandra; Berry, Colin
Abstract : Background: Displacement encoding with stimulated echoes (DENSE) encodes myocardial tissue displacement into the phase of the MRI image permitting direct quantification of myocardial displacement at multiple cardiac phases. Strain-encoded CMR with DENSE has high spatial (3.2 mm × 3.2 mm × 8 mm) and temporal resolution (TR= 27.34 ms). We aimed to measure myocardial strain values with DENSE in healthy adults across a broad age range at 3.0Tesla. Methods: Healthy volunteers with no prior medical history or treatment were enrolled and underwent CMR at 3.0T (Magnetom Verio, Siemens, Erlangen, Germany). Mid-left ventricular short axis and horizontal long axis DENSE sequences were obtained, and analysed using CIM_DENSE2D software (University of Auckland, New Zealand and Siemens Healthcare). Segmental and global myocardial circumferential (Ecc) and longitudinal (Ell) strain were obtained with DENSE. Results: 77 participants (mean (SD) age 43.0(16.9) years; range 18–78 years; 40 (52%) males;) were grouped into 3 tertiles according to age. Longitudinal strain differed according to age tertile with strain being greatest in individuals 35–55 years compared to younger or older subjects. There were no differences in Ecc according to age per tertile (Table 1). Conclusion: Longitudinal myocardial strain, as revealed by strain-encoded CMR, is associated with chronological age in healthy adults. Funding: Medical Research Scotland project grant. Professor Berry was supported by a Senior Clinical Fellowship from the Scottish Funding Council.